Effectiveness of Cognitive Rehabilitation Therapy in Enhancing Positive Emotion Expression Tools for Elderly People with Dementia in Tehran - Faramarzpour, Parisa; Moraveji, Mahtab (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study aimed to evaluate the effectiveness of Cognitive Rehabilitation Therapy (CRT) in enhancing positive emotional expression in elderly individuals with dementia in Tehran. Methods and Materials: A quasi-experimental design was employed with a pretest-posttest-follow-up approach. A total of 60 elderly individuals diagnosed with dementia were randomly assigned to either an experimental group (n = 30) receiving CRT or a control group (n = 30) that did not receive any intervention. The CRT program, lasting 8 weeks, focused on improving cognitive functions such as memory, attention, and executive functions, with an emphasis on fostering positive emotional expression. The Positive Emotion Expression Scale (PEES) was administered at three time points: pre-intervention, post-intervention, and at a 3-month follow-up. Data were analyzed using repeated-measures ANOVA and Bonferroni post-hoc tests. Results: The results revealed significant improvements in positive emotional expression in the experimental group across all time points. Specifically, repeated-measures ANOVA showed significant effects of time (F = 106.78, p = 0.001), group (F = 28.91, p = 0.001), and their interaction (F = 95.68, p = 0.001). Bonferroni post-hoc tests confirmed that improvements in positive emotional expression were significant between pretest and posttest (p = 0.001), and pretest and follow-up (p = 0.001), with a moderate effect size. Conclusion: These findings indicate that CRT significantly enhanced emotional expression in elderly individuals with dementia. Cognitive Rehabilitation Therapy was found to be an effective intervention for improving positive emotional expression in elderly individuals with dementia. This suggests that CRT can be a valuable tool in managing emotional and cognitive challenges associated with dementia, ultimately contributing to a better quality of life for this population.